Corpus Linguistics, Context and Culture - Mahlberg, Michaela; Wiegand, Viola (Diskursmuster ;, 2019)
Corpus Linguistics, Context and Culture demonstrates the potential of corpus linguistic methods for investigating language patterns across a range of contexts. Organised in three sections, the chapters range from detailed case studies on lexico-grammatical patterns to fundamental discussions of meaning as part of the 'discourse, contexts and cultures' theme. The final part on 'learner contexts' specifically emphasises the need for mixed-method approaches and the consideration of pedagogical implications for real world contexts. Beyond its contribution to current debates in the field, this edited volume indicates new directions in cross-disciplinary work.